Educational Institutions of Higher Education as Development Driver of Nuclear Power Plant Areas - N. F. Privalova; V. A. Rudenko; I. A. Bublikova (Глобальная ядерная безопасность)
The paper considers a new approach to the formation of development models of cities of nuclear industry enterprises which is defined as infrastructural-service oriented assuming not only providing residents with modern infrastructure, but also with advanced services, putting the most effective satisfaction of human needs and demands in the city at the forefront. The paper analyzes the impact that universities have on the economy, the level of human capital and innovation potential of the territory of the region in connection with the expansion of university functions and the change in the vector of the functional model of the university - from a universal scientific and educational to an expert-technological one. In recent years, in response to the current challenges in our country, the functions of universities have been transformed, with the main functions (educational and research) emphasizing the function of serving the regional community, in the implementation of which the university acts as a driver of territory development. The article reveals the directions and forms of activities of Volgodonsk Engineering and Technical Institute as a driver of development of Volgodonsk and Volgodonsk agglomeration as a territory of Rostov NPP location.